Pengaruh Media Pembelajaran Educaplay Terhadap Hasil Belajar Pendidikan Pancasila Siswa Sekolah Dasar - Rumaiya, Ikmatul; Sya'ban, Moh. Balya Ali (Universitas Nahdlatul Ulama Blitar, 2025)
The Pancasila Education subject with Educaplay is one of the uses of learning media that can encourage students to have an interest in thinking critically, responsibly, creatively and developing the student learning process in order to get maximum learning results. The learning outcomes of Pancasila education are considered to still have a very big influence on students because it can be seen from the connectedness related to everyday life, but there is a problem faced by students at SDN Baru 06, namely the lack of learning outcomes. Through field observations, there are findings that show that learning outcomes at SDN Baru 06 are still relatively low. This can be seen through learning results and observations made in class. This situation is caused by conventional learning model factors, which cause students to become passive and uninterested in lessons, due to the rare use of technology-based learning media. By using media through the Educaplay platform, it can help students' learning process so that learning outcomes can be achieved well and continue to improve. The results of statistical analysis show that the Educaplay learning media has an effect on the experimental class through the pre-test and post-test which has been found to have significant achievement results in the ability of class V learning outcomes at SDN Baru 06 Jakarta.